ปัจจัยที่มีความสัมพันธ์กับการมารับการรักษาของผู้ป่วยโรคหลอดเลือดสมองขาดเลือดระยะเฉียบพลัน - นิพาพร ภิญโญศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purpose of this descriptive research was to study the relationships between age, sex, stroke knowledge, stroke severity, stroke bystander, and location of onset with seeking treatment of acute ischemic stroke patients. Samples were 120 male and female, were 20-59 years old and were acute ischemic stroke patients admitted at Vajira Hospital. Research instruments: Stroke Knowledge Scale, Stroke Severity Scale, and NIHSS. They had been tested for their content validity and reliability. The reliability were .80, and .84, respectively, and NIHSS Interrater retest were .95, and .96, respectively. Statistical techniques used in data analysis were mean, median, standard deviation, and Chi-Square test. The findings were as follows: 1. There were 20 % of acute ischemic stroke patients that had early seeking treatment within 3 hours after the onset of symptoms.2. There were significant relationships between stroke severity, stroke bystander, and location of onset with seeking treatment of acute ischemic stroke patients (p<.05; X²= 31.02, X²= 21.74, and X²= 31.27, respectively) but there were no relationships between age, sex, and stroke knowledge with seeking treatment of acute ischemic stroke patients (p>.05).